2011
DOI: 10.1371/journal.ppat.1002019
|View full text |Cite
|
Sign up to set email alerts
|

SUMO-Interacting Motifs of Human TRIM5α are Important for Antiviral Activity

Abstract: Human TRIM5α potently restricts particular strains of murine leukemia viruses (the so-called N-tropic strains) but not others (the B- or NB-tropic strains) during early stages of infection. We show that overexpression of SUMO-1 in human 293T cells, but not in mouse MDTF cells, profoundly blocks N-MLV infection. This block is dependent on the tropism of the incoming virus, as neither B-, NB-, nor the mutant R110E of N-MLV CA (a B-tropic switch) are affected by SUMO-1 overexpression. The block occurred prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 87 publications
(117 reference statements)
3
62
1
1
Order By: Relevance
“…To validate the interaction between BGLF4 and SUMO2, we first performed an in vitro pulldown assay using GST-SUMO2, a GST-SUMO2 tandem trimer [GST-(SUMO2) 3 ], and lysate from Flag-BGLF4-transfected cells. We found that both GST-SUMO2 and GST-(SUMO2) 3 , but not the GST control, bound BGLF4 (Fig. 1A, upper).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the interaction between BGLF4 and SUMO2, we first performed an in vitro pulldown assay using GST-SUMO2, a GST-SUMO2 tandem trimer [GST-(SUMO2) 3 ], and lysate from Flag-BGLF4-transfected cells. We found that both GST-SUMO2 and GST-(SUMO2) 3 , but not the GST control, bound BGLF4 (Fig. 1A, upper).…”
Section: Resultsmentioning
confidence: 99%
“…SUMOylation regulates the transcriptional activity of ZTA and RTA (10,13,14,45,47,80). Noncovalent SUMO-protein interactions can also occur through a SUMO interaction motif (SIM) in the target proteins (3,57,90,91,93). EBNA3C contains a SIM motif and upregulates EBNA2-mediated gene activation by binding to a SUMOylated protein (84).…”
Section: E Pstein-barr Virus (Ebv) First Discovered In Association Withmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM5α contains B boxes, a coiled-coil domain, and a RING domain, and can function as an E3 ubiquitin ligase (Reymond et al, 2001). In addition, TRIM5α contains a SPRY/B30.2 domain with two SUMO-interaction motifs (SIMs), which are required for N-MLV restriction (Arriagada et al, 2011). This SPRY/B30.2 domain can also directly bind with the HIV capsid, and is believed to be critical for HIV restriction (Sawyer et al, 2005; Stremlau et al, 2005; Luban, 2007; Ganser-Pornillos et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TRIM5α-mediated ubiquitin conjugation is required for HIV-1 capsid destabilization and inhibition of reverse transcription (Campbell et al, 2016). Interestingly, SIM mutations in TRIM5α not only lead to loss of restriction capability against N-MLV (Arriagada et al, 2011), but the mutations also prevent TRIM5α from shuttling into the cell nucleus, thus rendering it unable to restrict incoming HIV retrovirion cores (Brandariz-Nunez et al, 2013). …”
Section: Introductionmentioning
confidence: 99%